Characterizing the Assessment and Management of Vitamin D Levels in Patients with Osteoporosis in Clinical Practice: A Chart Review Initiative - Jonathan D. Adachi; Jacques P. Brown; George Ioannidis (Journal of Osteoporosis)
Though vitamin D is important for bone health, little is known about the monitoring and management of vitamin D levels in patients with osteoporosis in clinical practice—a deficit this chart review initiative aimed to remedy. A total of 52 physicians completed profiles for 983 patients being treated for osteoporosis between November 2008 and April 2009. Information collected included demographics; fracture risk factors; availability and level of serum vitamin D measurements; and information on osteoporosis medications and calcium and vitamin D supplementation. Physicians also evaluated patients’ current regimens and detailed proposed changes, if applicable. Nearly 85% of patients were prescribed calcium and vitamin D supplements. Serum 25-hydroxy vitamin D levels were available for 73% of patients. Of these patients, approximately 50% had levels less than 80 nmol/L, which contrasts with the 37% thought to have “unsatisfactory” vitamin D levels based on physician perceptions. Physicians felt 26% of patients would benefit from additional vitamin D supplementation. However, no changes to the osteoporosis regimen were suggested for 48% of patients perceived to have “unsatisfactory” vitamin D levels. The results underscore the importance of considering vitamin D status when looking to optimize bone health.